Molecular docking of the bioactive compound Ocimum sanctum as an inhibitor of Sap 1 Candida albicans - Gusnia Meilin Gholam (Sasambo Journal of Pharmacy, 2022)
Candida albicans (C. albicans) is the norm microbiota that lives in humans' oral cavity, digestive tract, and urinary tract. However, C. albicans, under certain circumstances can cause superficial infections of the mucosa such as oropharyngeal candidiasis (OPC) or vulvovaginal candidiasis (VVC) and even systemic infections. Secreted aspartic proteinase (Sap) 1 plays a role in the phenotype change of C. albicans. The study aimed to perform molecular docking using the bioactive compound Ocimum sanctum to inhibit Sap 1 C. albicans. Methods used include preparation of protein structures, ligands preparation, simulation of docking, and analysis and visualization. The results showed Apigenin had the highest binding energy of 7,792 kcal/mol and was followed by methyl eugenol ligand 5,361 kcal/mol, Citral 5,307 kcal/mol, Ursolic acid 4,967 kcal/mol, and Taxol 2,118 kcal/mol. Known interactions from the docking results showed that the four ligands hit the catalytic residue Asp32/Asp218, but only ursolic acid did not hit the catalytic residue. This study concludes that all ligands have binding energies that inhibit Sap 1, resulting in various interactions, amino acid residue contacts, and dissociation constants.